Urgensi Penegakan Hukum Terkait Kejatahan Tindak Pidana Suap Dalam Etika Profesi Advokat - Iqbal Yudha Pratama; Miswar Nasution; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
In Indonesia, Law Enforcement Officials, Including Judges, Prosecutors, Police, And Advocates, Are Responsible For Delivering Justice. Advocates Are Law Enforcement Officers Who Assist Clients Seeking Justice In The Legal System And Provide Legal Aid Services. Assistance Is The Process Of Making It Easier For Clients To Solve Problems When Dealing With The Legal Process. Advocates Are Obliged To Uphold Human Rights And Devote Themselves To The Interests Of Society Rather Than Themselves, Making Their Profession A Noble One. However, It Turns Out That Many Advocates Have Stated That They Have Committed Crimes Since 2005, At Least 22 Advocates Have Been Charged With Corruption Cases, 16 Advocates Have Committed Bribery, Two Advocates Have Provided Inaccurate Information, And Four Others Have Obstructed Investigations. The Results And Discussion Of The Research Show That Criminal Cases Of Bribery Committed By Advocates Can Be Tried By The State Through Law In Statutory Regulations As Stipulated In The Criminal Code, The TPS Law, And The PTPK Law. This Study Aims To How To Enforce The Law On The Crime Of Bribery Committed By Advocates In Carrying Out Their Duties And Profession. The Method Used In This Study Is A Normative Juridical Method By Taking An Approach Through Statutory Regulations. Keywords: Crime, Law Enforcement, Justice